Gravity, Geoid and Earth Observation IAG Commission 2: Gravity Field, Chania, Crete, Greece, 23-27 June 2008 - Mertikas, Stelios P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
These Proceedings include the written version of papers presented at the IAG International Symposium on "Gravity, Geoid and Earth Observation 2008". The Symposium was held in Chania, Crete, Greece, 23-27 June 2008 and organized by the Laboratory of Geodesy and Geomatics Engineering, Technical University of Crete, Greece. The meeting was arranged by the International Association of Geodesy and in particular by the IAG Commission 2: Gravity Field. The symposium aimed at bringing together geodesists and geophysicists working in the general areas of gravity, geoid, geodynamics and Earth observation. Besides covering the traditional research areas, special attention was paid to the use of geodetic methods for: Earth observation, environmental monitoring, Global Geodetic Observing System (GGOS), Earth Gravity Models (e.g., EGM08), geodynamics studies, dedicated gravity satellite missions (i.e., GOCE), airborne gravity surveys, Geodesy and geodynamics in polar regions, and the integration of geodetic and geophysical information.
Gravimetry (Terrestrial, Shipborne, Airborne) and Gravity Networks -- Space-Borne Gravimetry: Present and Future -- Earth Observation by Satellite Altimetry and InSAR -- Geoid Modeling and Vertical Datums -- Regional Gravity Field Modeling -- Global Gravity Field Modeling and EGMO8 -- Temporal Gravity Changes and Geodynamics -- Earth Observation and the Global Geodetic Observing System (GGOS) -- Geodetic Monitoring of Natural Hazards and a Changing Environment.
Keywords: Geography; Physical geography; Earth Sciences; Earth Sciences, general; Geophysics/Geodesy.; Geotechnical Engineering & Applied Earth Sciences; Earth Sciences, general; Earth Sciences, general